RANCANG BANGUN SISTEM INFORMASI E-ORDER DI PUJASERA KERTOSONO - Siti Faizatul Ummah; Munawarah -; Moh. Anshori Aris Widya (SAINTEKBU, 2018)
Business competition between coffee shops in Kertosono is very tight. So, to stand in this competition, different and unique services are needed to make it fairer. The transfer of manual to computerized systems can be an alternative way. This research was conducted at Cafe Pujasera Kota Kertosono. Researchers use interviews, observations, and literature studies as a collection of data. System design in this research is systemic and sequential. The result of observations, Cafe Pujasera still uses the conventional system. customer order was conducted by waitress which continued to the kitchen. Sales report count based on bill archives was printed by the cashier. The Solution is a self-service and paperless concept. Customer reserve the menu on the system which integrated with the cashier and kitchen. The system gives automatic notification to the kitchen to process the reserve menu. Bill and Report also can be printed directly from the system and can give the better service to the customer. Keywords: Information System, Order Menu, PHP, MySQL.